Vibration control of a structure by a tuned liquid column damper with embossments. (1st August 2018) - Park, ByungJin; Lee, YongJae; Park, MinJae; Ju, Young K.
Highlights: The ETLCD exhibited non-linearity similar to that of conventional TLCD. The evaluation equations of the equivalent damping ratio were proposed. Experimental natural frequencies of TLCD and ETLCD were overestimated. The adjusting factor for calculating effective length was proposed. The control performance of ETLCD was superior to that of conventional TLCD. Abstract: Several studies have examined damping mechanisms to improve damping effects in a tuned liquid column damper (TLCD). The additional damping mechanisms include orifices, valves, and the use of highly viscous liquids. In the present study, in contrast to previous studies, a damping mechanism using embossments on the wall of the TLCD was proposed, and TLCD with embossment (termed as ETLCD) was proposed as a new type of passive damper. The study focuses on an experimental evaluation of the dynamic characteristics of ETLCD and vibration control performance for tall buildings with ETLCD by using a shaking table. Thus, a characteristic experiment was performed with the presence of embossments, total length of the liquid column, and an excitation amplitude ratio as variables. Additionally, a scaled model test of the SDOF building composed of a free vibration test and sine sweep forced vibration test was conducted to verify the vibration control performance of the structure with ETLCD. Consequently, the equivalent damping ratios of conventional TLCD and ETLCD were experimentally compared, and the theoretical natural frequency of TLCD was re-evaluated in the characteristic experiment. Furthermore, the results of the scaled model test indicated that the vibration control performance of the ETLCD was superior to that of the conventional TLCD in terms of response reduction, efficiency, and stability.